Metabolic syndrome accelerates epigenetic ageing in older adults: Findings from The Irish Longitudinal Study on Ageing (TILDA). - Mc Crory, Cathal; O'Halloran, Aisling; Kenny, Rose; Fallon, Padraic (My University, 2023)
Metabolic syndrome (MetS) is a risk factor for the development of diabetes, cardiovascular disease, and all-cause mortality. It has an estimated prevalence of 40 % among older adults. Epigenetic clocks, which measure biological age based on DNA methylation (DNAm) patterns, are a candidate biomarker for ageing. GrimAge is one such clock which is based on levels of DNAm at 100 Cytosine-phosphate-Guanine (CpG) sites. This study hypothesised that those with MetS have ‘accelerated ageing’ (biological age greater than their chronological age) as indexed by GrimAge. This study examined MetS's association with GrimAge age acceleration (AA) using data from a subsample of 469 participants of the Irish Longitudinal Study on Ageing (TILDA). MetS was defined by National Cholesterol Education Program Third Adult Treatment Panel (ATP III) and International Diabetes Foundation (IDF) criteria, operationalised using the conventional binary cut-off, and as a count variable ranging from 0 to 5, based on the presence of individual components. This study also explored inflammation (as measured by C reactive protein) and metabolic dysfunction (as measured by adiponectin) as possible mediating factors between MetS and GrimAge AA. We found that MetS as defined by IDF criteria was associated with GrimAge AA of 0.63 years. When MetS was treated as a count, each unit increase in MetS score was associated with over 0.3 years GrimAge AA for both ATP III and IDF criteria. Inflammation mediated approximately one third of the association between MetS and GrimAge AA, suggesting that chronic subclinical inflammation observed in MetS has a relationship with DNAm changes consistent with a faster pace of ageing. Metabolic dysfunction mediated the association between MetS and GrimAge AA to a lesser extent (16 %). These data suggest that chronic subclinical inflammation observed in MetS has a relationship with DNAm changes consistent with a greater pace of ageing.
PUBLISHED
Keywords: Mediation; GrimAge; Epigenetics; Metabolic syndrome; Accelerated ageing; Ageing; Ageing, stroke, dementia; Biomedical sciences; Epidemiology; Other